Evaluasi Kesiapan Mahasiswa Pendidikan Biologi untuk Menjadi Guru - Dian Samitra; Hadiwinarto Hadiwinarto (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to evaluate the readiness of Biology Education Students at STKIP-PGRI Lubuklilnggau to become teachers based on Pedagogical Content Knowledge (PCK). The method used is the descriptive method. The research subjects were 23 Biology Education Students at STKIP-PGRI Lubuklinggau in the 7th semester of the 2021/2022 academic year. Data Content Knowledge (CK), Pedagogical Knowledge (PK), and Pedagogical Content Knowledge (PCK) were collected using a questionnaire, while data on students' abilities in making lesson plans and teaching abilities were collected through assessment sheets that STKIP-PGRI Lubuklinggau had prepared. The study results obtained that CK, PK, PCK, the ability to make lesson plans and the ability to teach students were categorized as good. In conclusion, the Biology Education Student of STKIP-PGRI Lubuklinggau is ready to become a teacher. Keywords: Evaluation, Teachers, Students, Pedagogical Content